PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DANA HIBAH DI KABUPATEN BENGKALIS - Zikri Yohanda Khairi; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
One of the criminal acts which can be said to be phenomenal is the problem of corruption. Corruption in Indonesia as it has already become a culture that developed among the upper-class society down. As a district that has a large Regional Government Budget, Bengkalis Regency has a huge potential going criminal offence of corruption, especially on social assistance grants and funds are budgeted in a Regional Government Budget each year. Corruption in the Regency of Bengkalis grants funds to occur in 2012 and has been reported to the police starting in October 2013, but until now in 2017, only 7 people who are punished, 1 in the status of the suspect and still leaves 5 other presumed do corruption of this grants. As for the writing of theses goals, namely: first, the crime of corruption of law enforcement grants and social assistance. Second, the barriers in law enforcement corruption criminal act social assistance grants and funds. Third, efforts are being made to overcome the barriers in law enforcement criminal acts of corruption.The research was sociological legal research i.e. Research wants to see unity between law and society by the existence of a gap between the das sollen and das sein. This research was conducted in the area of the Regency of Bengkalis, while population and the sample is the entire parties concerned with the issue examined in this study, the data source used, the primary data, secondary data and data tertier, techniques of collecting data in this study was conducted through interviews and research librarianship.From the results of the research there are three basic issues that can be inferred. First, in the conduct of law enforcement corruption criminal act social assistance grants and funding, investigators and the public prosecutor made efforts of law enforcement in pereventif as well as repressive. Second, the obstacles faced by the Ditreskrimsus Police State Attorney's Bengkalis Riau and there are two factors, namely the internal factors and external factors. Third, efforts are being made in overcoming internal obstacles that is to increase the number of personnel, minimize expenses for tapping the Fund operations, and coordinate with relevant agencies-agencies. While the effort of overcoming obstacles Externa is renting a House as a place of temporary office and split the teams and collect witnesses assisted by relevant agencies.The author's suggestion, first, improving supervision and involves an active role in the celebrated by law enforcement corruption criminal act social assistance grants and funds. Secondly, the efficiency of the body's internal law enforcement either Police or District Prosecutor General as well as the efficiency of external factors. Third, enforcing the law in a professional manner as well as providing criminal sanctions against the perpetrators of the crime of corruption funds grants.Keywords: Law Enforcement – Criminal Act – Corruption – Grants